1997
DOI: 10.1073/pnas.94.7.3134
|View full text |Cite
|
Sign up to set email alerts
|

Promoter-creating mutations in Pseudomonas putida : A model system for the study of mutation in starving bacteria

Abstract: A novel experimental system to study mutation in starving bacteria was designed, relying on the activation of a promoterless phenol degradation operon of Pseudomonas putida. The Phe ؉ (phenol-utilizing) mutants accumulated in the starving culture of P. putida in the presence of phenol but not in the absence of it. We ruled out the possibility that the absence of phenol eliminates Phe ؉ mutants from the starving population. Sequence analysis of the Phe ؉ mutants revealed that base substitutions, deletions, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
91
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(97 citation statements)
references
References 55 publications
(54 reference statements)
2
91
2
Order By: Relevance
“…The result of the mechanism(s) responsible for this phenomenon is the production of mutations that arise in nondividing or stationary-phase bacteria when the cells are subjected to nonlethal selective pressure, such as nutrientlimited environments (6,11,15,32,61). While most of the research has involved Escherichia coli model systems, similar observations have been made in other prokaryotes (43) as well as in eukaryotic organisms (69).…”
mentioning
confidence: 92%
“…The result of the mechanism(s) responsible for this phenomenon is the production of mutations that arise in nondividing or stationary-phase bacteria when the cells are subjected to nonlethal selective pressure, such as nutrientlimited environments (6,11,15,32,61). While most of the research has involved Escherichia coli model systems, similar observations have been made in other prokaryotes (43) as well as in eukaryotic organisms (69).…”
mentioning
confidence: 92%
“…Both of these classes have been shown to play important roles across a wide range of taxa, from vertebrates (1, 2) to bacteria (3,4), and their relative importance has been the topic of considerable discussion (5)(6)(7)(8)(9)(10)(11)(12). Significantly, many previous studies have addressed these questions by focusing on single instances of functional innovation (13)(14)(15)(16) or selective regimes (17)(18)(19)(20)(21)(22). However, to identify general principles, it is necessary to study evolutionary innovation for a large number of different functions in parallel.…”
mentioning
confidence: 99%
“…In previous studies on adaptation to utilize phenol using recombinant strains, mutations were found in the promoter region which resulted in constitutively active 0''-dependent promoters (Burchhardt et al, 1997;Kasak et al, 1997;Nurk et al, 1993). The adaptation mechanism of strain T A N 1 was quite different because a mutation was not found in the promoter region.…”
Section: Discussionmentioning
confidence: 99%
“…strain EST1001 (Kivisaar et al, 1989), tbuD from Pseudomonas pickettii PKOl (Kukor & Olson, 1992) or pheA from Bacillus stearothermophilus BR219 (Kim & Oriel, 1995). Recently, mutations that allow P. putida or Escherichia coli to utilize phenol as a carbon source have been reported (Burchhardt et al, 1997;Kasak et al, 1997;Nurk et al, 1993). These studies used recombinant strains transformed with exogenous genes for phenol degradation.…”
Section: Introductionmentioning
confidence: 99%